Efektivitas program MIPA Learning Quranic dalam membangun paradigma Qurani mahasiswa Universitas Lambung Mangkurat - Maisarah; Mailita; Agung Setyo Wiranto; Juwita Lasterina (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
The MIPA Learning Quranic (MLQ) program aims to provide Islamic religious education and Tahsin of the Quran and support the curriculum of compulsory Islamic courses for new Muslim students of FMIPA ULM. Data collection techniques in this study used observation, tests, questionnaires, and documentation. After the data is collected, it is processed using qualitative and quantitative descriptive analysis (mixed method). This method is used to describe how the MLQ program is implemented and to find out how effective the MLQ program is at FMIPA ULM. The results of this study revealed that the highest frequency of acquisition of pre-test scores, namely B and B+, was 53% of the total participants, while the lowest frequency was A+. After the MLQ activity was completed, the final ability test (post-test) was carried out. The frequency of the highest post-test scores, namely B+, and those who obtained A and A+ scores increased, while the frequency of C scores decreased compared to the pre-test results. Therefore, this MLQ program can be said to be effective in building the Quranic paradigm because it produces output scores ​​(post-test) that are better than input scores (pre-test) and can improve the literacy and understanding of the Quran for new students FMIPA ULM.